Hybrid Biomaterial Initiates Refractory Wound Healing via Inducing Transiently Heightened Inflammatory Responses. Issue 21 (23rd May 2022) - Liu, Xuemei; Dou, Geng; Li, Zihan; Wang, Xiangdong; Jin, Ronghua; Liu, Yao; Kuang, Huijuan; Huang, Xiaoyao; Yang, Xiaoxue; Yang, Xiaoshan; Liu, Siying; Wu, Meiling; et al.
Abstract: Inflammation plays a crucial role in triggering regeneration, while inadequate or chronic inflammation hinders the regenerative process, resulting in refractory wounds. Inspired by the ideal regeneration mode in lower vertebrates and the human oral mucosa, realigning dysregulated inflammation to a heightened and acute response provides a promising option for refractory wound therapy. Neutrophils play important roles in inflammation initiation and resolution. Here, a hybrid biomaterial is used to stimulate transiently heightened inflammatory responses by precise tempospatial regulation of neutrophil recruitment and apoptosis. The hybrid biomaterial (Gel@fMLP/SiO2 ‐FasL) is constructed by loading of formyl‐met‐leu‐phe (fMLP) and FasL‐conjugated silica nanoparticles (SiO2 ‐FasL) into a pH‐responsive hydrogel matrix. This composition enables burst release of fMLP to rapidly recruit neutrophils for heightened inflammation initiation. After neutrophils act to produce acids, the pH‐responsive hydrogel degrades to expose SiO2 ‐FasL, which induces activated neutrophils apoptosis via FasL‐Fas signaling triggering timely inflammation resolution. Apoptotic neutrophils are subsequently cleared by macrophages, and this efferocytosis activates key signalings to promote macrophage anti‐inflammatory phenotypic transformation to drive regeneration. Ultimately, Gel@fMLP/SiO2 ‐FasL successfully promotes tissue regeneration by manipulating inflammation in critical‐sized calvarial bone defects and diabetic cutaneous wound models. This work provides a new strategy for refractory wound therapy via inducing transiently heightened inflammatory responses. Abstract : Inflammation plays a vital role in tissue regeneration, while an insufficient and prolonged inflammatory process will result in refractory wounds. A hybrid biomaterial is constructed here to manipulate inflammation to a transiently heightened process by precise tempospatial regulation of neutrophil recruitment and apoptosis, providing a new strategy for refractory wound therapy.